1983
DOI: 10.1002/chin.198345192
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: NONSTEROIDAL ANTIINFLAMMATORY AGENTS, X: ANTIPHLOGISTIC PYRAZOLE DERIVATIVES, II

Abstract: Pyrazolylalkylcarbonsäure‐Derivate (II) werden ausgehend vom Ester (I) nach literaturbekannten Verfahren hergestellt und auf entzündungshemmende Wirksamkeit getestet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Tetralkyl 1-hydroxy-1,1-bisphosphonates can be converted into tetrakis(trimethylsilyl) esters on treatment with bromotrimethylsilane [64] or iodotrimethylsilane [65,66], also a known behavior of dialkyl phosphonates [67] or dialkyl acylphosphonates [68]. Alternatively, tetrakis(trimethylsilyl) esters can be obtained by using chlorotrimethylsilane with sodium iodide [69].…”
Section: Dealkylation Of Esters By Me 3 Sixmentioning
confidence: 99%
“…Tetralkyl 1-hydroxy-1,1-bisphosphonates can be converted into tetrakis(trimethylsilyl) esters on treatment with bromotrimethylsilane [64] or iodotrimethylsilane [65,66], also a known behavior of dialkyl phosphonates [67] or dialkyl acylphosphonates [68]. Alternatively, tetrakis(trimethylsilyl) esters can be obtained by using chlorotrimethylsilane with sodium iodide [69].…”
Section: Dealkylation Of Esters By Me 3 Sixmentioning
confidence: 99%
“…Our continuous studies have demonstrated the utilization of carbohydrates specially L-ascorbic acid and its analogs in the synthesis of heterocycles including pyrazoles, triazoles, imidazoles and isoxazolines [1][2][3][4][5]. The observation that triazole and pyrazole derivatives are biologically active compounds [6][7][8][9][10] specially as insecticides and antiflamatory has promoted the extension of our study to synthesize a new series of this class of compounds in the hope of producing more effective chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%